Cultivar Development of Kelps for Commercial Cultivation—Past Lessons and Future Prospects - Goecke, Franz; Klemetsdal, Gunnar; Ergon, Åshild (Frontiers in Marine Science, 2020)
Cultivated kelps and other macroalgae have great potential in future provision of food, feed, bioenergy, fertilizer, and raw material for a range of chemical products including pharmaceuticals, food and feed additives, and cosmetics. Only a few species are currently cultivated, almost exclusively in Asia. There is a range of species that could be utilized in different parts of the world, providing that protocols for reproduction, propagation, and cultivation are developed. Domestication of species involves selection of traits that are desirable in cultivation and in the utilization of the harvested biomass. Genetic improvement of cultivated species through recombination of alleles and selection (breeding) has ensured high productivity and product quality in both agri- and aquaculture and will likely do so for macroalgae cultivation and use as well. According to the published literature, genetic improvement of kelps in Asia has so far largely relied on utilization of heterosis expressed in certain combinations of parental material, sometimes species hybrids. Here, we explore and evaluate the various methods that could be used in kelp breeding and propose an initial simple and low-cost breeding strategy based on recurrent mixed hybridization and phenotypic selection within local populations. We also discuss the genetic diversity in wild populations, and how this diversity can be protected against genetic pollution, either by breeding and cultivating local populations, or by developing cultivars that are not able to establish in, or hybridize with, wild populations.